Drying Cocoa, Trinidad, B.W.I. - (:unkn) unknown (Stephens Ltd., Trinidad, 2010)
A picture of workers spreading the cocoa beans on a row of cocoa houses for drying in the sun.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cocoa--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Agricultural laborers--Trinidad and Tobago; Cocoa trade--Trinidad and Tobago; Cocoa processing--Trinidad and Tobago; Working class--Trinidad and Tobago; Cocoa houses